Study on Spatiotemporal Distribution Characteristics of Rainfall Erosivity in “Three-Lake” Basin of Central Yunnan - YANG Wenchun; GU Guihua; ZHU Weibing; HUO Shouhua (Renmin Zhujiang)
This study is conducted to explore the influence of rainfall on the characteristics of soil erosion in the “three-lake” basin of Fuxian Lake,Xingyun Lake,and Qilu Lake in central Yunnan.On the basis of the daily rainfall observation data of four precipitation stations in the basin from 1992 to 2020,namely,the Liangwanghe,Haikou,Chaershan,and Shagouzui Stations,the daily rainfall erosivity model is employed to calculate rainfall erosivity.Then,its temporal variation characteristics are analyzed with the M-K method,and the spatial changing laws of rainfall and rainfall erosivity are investigated by the Kriging interpolation method for spatial interpolation.The results are as follows:From 1992 to 2020,the average annual rainfall in the “three-lake” basin is 907.6 mm,and the average annual rainfall erosivity is 3 088~4 172 MJ·mm/(hm2·h);the variation coefficient of annual rainfall erosivity is between 0.25 and 0.32,and the number of days with erosive rainfall at each station is 686~759.There is a good correlation between annual rainfall and annual rainfall erosivity,and the annual rainfall erosivity in the basin fluctuates on the whole,with no significant increasing trend and no abrupt change.The rainfall erosivity varies significantly within the year,with that in summer accounting for 61.4% and that in the flood season accounting for 90.5% of the year,and the variation of rainfall erosivity is topped by summer,followed by autumn,spring,and winter.The spatial distribution trend of average annual rainfall erosivity in the basin is consistent with the annual rainfall distribution trend,high in the north and low in the south.The rainfall erosivity decreases gradually from north to south in terms of years,flood seasons,summer,and autumn,while in terms of non-flood seasons,spring,and winter,rainfall erosivity decreases from northeast to southwest.The research results can provide a scientific basis for water and soil conservation and ecological protection of lakes in the basin of plateau lakes in central Yunnan.